Two Strikes in the Cath Lab: Lessons from Repeat Aneurysm Ruptures During Endovascular Treatment - Vita Kusuma Rahmawati; Achmad Firdaus Sani; Dedy Kurniawan; Faishol Hamdani; Muh. Wildan Yahya (Journal of Neurointervention and Stroke, 2026)
Highlight: Repeat aneurysm rupture during endovascular therapy is rare but often fatal This case highlights the need for careful hydrocephalus management and monitoring Dynamic neurological assessment guides urgent aneurysm repair and improves outcomes ABSTRACT Introduction: Repeat aneurysmal rupture in the catheterization laboratory remains a critical concern, with periprocedural mortality rates reported as high as 63%. Such rebleeding requires rapid multidisciplinary decision-making, particularly in high-grade aneurysmal subarachnoid hemorrhage (aSAH) complicated by hydrocephalus. Case: A 56-year-old hypertensive man presented with sudden-onset headache followed by loss of consciousness (Hunt and Hess grade III). Computed tomography (CT) revealed subarachnoid and intraventricular hemorrhage, and CT angiography identified a left saccular posterior communicating artery aneurysm. During induction in the catheterization laboratory, he developed severe headache, seizures, hypertension, and pupil anisocoria, raising concern for impending cerebral herniation. Owing to a postictal comatose state, his clinical Hunt and Hess grade deteriorated to grade V. Emergent CT confirmed acute hydrocephalus and rebleeding. Endovascular coiling was deferred, and an external ventricular drain was placed, resulting in improved consciousness. Subsequent angiography demonstrated contrast extravasation from the aneurysm dome, confirming rebleeding. The aneurysm ruptured three times over two weeks, including twice during separate catheterization laboratory sessions. Definitive endovascular coiling ultimately achieved near-complete aneurysm packing. Neurological status improved to Hunt and Hess grade II, followed by ventriculoperitoneal shunt placement. At discharge, the modified Rankin Scale score improved from 4 to 3 without new focal neurological deficits. Three-month follow-up confirmed stable neurological recovery. Conclusion: This case highlights the challenges of repeated aSAH rupture in the catheterization laboratory, emphasizing hydrocephalus management and dynamic Hunt and Hess grading to guide aneurysm treatment timing. Urgent endovascular coiling may be warranted despite clinical instability, using individualized strategies to optimize neurological outcomes.